2007
DOI: 10.1007/s10886-007-9399-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis)

Abstract: Locoweeds (Astragalus and Oxytropis spp. that contain the toxic alkaloid swainsonine) cause widespread poisoning of livestock on western rangelands. There are 354 species of Astragalus and 22 species of Oxytropis in the US and Canada. Recently, a fungal endophyte, Embellisia spp., was isolated from Astragalus and Oxytropis spp. and shown to produce swainsonine. We conducted a survey of the major locoweeds from areas where locoweed poisoning has occurred to verify the presence of the endophyte and to relate end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 20 publications
14
109
0
Order By: Relevance
“…Considering the life cycle and host colonization of vertically transmitted fungal endophytes, it is possible that the same endophyte occurs throughout the plant. Systemic endophytic colonization in the apoplast of leaves, stems, and reproductive structures has been documented for several Astragalus species (Ralphs et al, 2008). If this is the case here, it may explain the occurrence of Se 0 in the seedling root, the taproot, and particularly the stem.…”
Section: Discussionmentioning
confidence: 54%
“…Considering the life cycle and host colonization of vertically transmitted fungal endophytes, it is possible that the same endophyte occurs throughout the plant. Systemic endophytic colonization in the apoplast of leaves, stems, and reproductive structures has been documented for several Astragalus species (Ralphs et al, 2008). If this is the case here, it may explain the occurrence of Se 0 in the seedling root, the taproot, and particularly the stem.…”
Section: Discussionmentioning
confidence: 54%
“…It has been observed that a fungal endophytic species occurring in locoweeds, the vertically-transmitted Undifilum oxytropis [324,325], previously described as Embellisia sp. [326,327], is capable to produce swainsonine in vitro. Novel species of Undifilum, U. fulvum and U. cinereum, have been later reported for production of this compound, respectively in Astragalus lentiginosus and A. mollissimus [328], along with strains of an unidentified Undifilum sp.…”
Section: Other Alkaloidsmentioning
confidence: 99%
“…4 The concentration of swainsonine also varies within a species and within a population of a species. For example, some populations of Lambert locoweed (O. lambertii), and plants within each population of white, woolly, and spotted locoweed, contain very low levels of the endophyte, thereby producing only trace amounts of swainsonine.…”
Section: Development Of a Biomarker For Locoweed Poisonings By K Welchmentioning
confidence: 99%
“…For example, some populations of Lambert locoweed (O. lambertii), and plants within each population of white, woolly, and spotted locoweed, contain very low levels of the endophyte, thereby producing only trace amounts of swainsonine. 4 This suggests that the endophyte must grow and colonize the plant at some critical threshold before swainsonine is produced at toxic levels. Offspring from these plants also had low levels of the endophyte and only traces of swainsonine.…”
Section: Development Of a Biomarker For Locoweed Poisonings By K Welchmentioning
confidence: 99%